An open-source software for building and simulating ordinary differential equation models in biology - Brenno Lemos Melquiades dos Santos; Diego Augusto Silva Castro; Sávio Francisco Cirino da Paz; Davi Jannotti Coelho Pinheiro; Bárbara de Melo Quintela; Marcelo Lobosco; Alexandre Bittencourt Pigozzo (PLoS ONE, 2025)
Mathematical and computational modeling are transforming biological research by enabling detailed exploration of complex systems. However, building computational models of biological phenomena often demands expertise in mathematical modeling and programming, creating barriers for researchers without such backgrounds. Existing software tools for computational modeling are frequently complex, overly general, or proprietary, limiting their accessibility and usability. To overcome these challenges, we present ODE-Designer, an open-source software tool that facilitates the construction and simulation of Ordinary Differential Equation (ODE) models in biology. A central feature of ODE-Designer is its intuitive visual interface, designed to be user-friendly and accessible. The software includes a graphical user interface with a node-based editor that allows users to create models without writing code. It supports model simulation and automatically generates the corresponding code, enabling efficient model exploration and aiding students in understanding core modeling principles. We propose that ODE-Designer serves as a valuable resource for both research and education in computational biology, improving accessibility and promoting a quantitative perspective in biological research. The software is freely available at: https://github.com/ufsj-dcomp/ode-designer-rs/.